Physical-chemical properties of 5-(3-fluorophenyl)-4-amino-1,2,4-triazole-3-thiol s-derivatives - O. A. Bihdan; V. V. Parchenko (Zaporozhye State Medical University, 2017)
Introduction. Currently an attempt to combine 1,2,4-triazole heterocycle with various pharmacologically active fragments of other organic molecules is popular among the scientists. Earlier we have noted that the introduction of fluorophenyl radical in the 1,2,4-triazole structure leads to the formation of compounds with new properties and it stimulates and inspires scientists for further search of new compounds among 1,2,4-triazole-3-thiol fluorphenylderivatives. The aim of our study was to synthesize new derivatives of S-5-(3-fluorophenyl)-4-amino-1,2,4-triazole-3-thiol, to explore the physical and chemical properties for the first time obtained 3-(3-fluorophenyl)-6-(aryl-, heteryl)-[1,2,4]triazole[3,4-b][1,3,4] thiadiazole. Research materials and methods. The study of the physical and chemical properties of 5-(3-ftorfenyl)-4-amino-1,2,4-triazole-3-thiol and 3-(3-ftorfenyl)-6-(aryl-, heteryl)-[1,2,4]triazole[3,4-b][1,3,4]thiadiazoles has been conducted using certified and licensed equipment of physical and chemical laboratories in Zaporozhye State Medical University according to the plans of the study. Research results. The structure of the synthesized 3-(3-ftorfenyl)-6-(aryl-, heteryl)-[1,2,4]triazole[3,4-b][1,3,4]thiadiazoles has been proved using modern physical-chemical methods of analysis (elemental analysis, 1H NMR spectroscopy, chromatography-mass spectrometry), and their identity has been confirmed chromatographically. The signals of aromatic protons 3-(3-ftorfenyl)-6-(aryl-, heteryl)-[1,2,4]triazole[3,4-b][1,3,4]thiadiazoles in the 1H NMR-spectrum registered as doublets, triplets, multipletes and relevant chemical shifts. Analyzing the constants peaks of pseudomolecular ions of initial compound and corresponding 3-(3-ftorfenyl)-6-(aryl-, heteryl)-[1,2,4]triazole[3,4-b][1,3,4]thiadiazoles we can assert about the compliance between the calculated values of the mass and found mass in the analysis. Conclusions. Using the known methods of synthesis we have obtained for the first time the 5-(3-fluorophenyl)-4-amino-1,2,4-triazole-3-thiol which was cyclized in the presence of the relevant aryl-, heterylacetic acids in POCl3. We have obtained a whole series of new 3-(3-ftorfenyl)-6-(aryl-, heteryl)-[1,2,4]triazole[3,4-b][1,3,4]thiadiazoles. The reaction of cyclization and confirmation of the obtained molecules' structure have been proved by modern complex methods of analysis (elemental analysis, 1H NMR-spectroscopy, chromatography-mass spectrometry).